By Any Means Necessary: Urban Regeneration and the "State of Exception" in Glasgow's Commonwealth Games 2014. Issue 2 (6th August 2014) - Gray, Neil; Porter, Libby
Abstract When compulsory purchase for urban regeneration is combined with a sporting mega‐event, we have an archetypal example of what Giorgio Agamben called the "state of exception". Through a study of compulsory purchase orders (CPOs) on the site of the Athletes' Village for Glasgow's 2014 Commonwealth Games, we expose CPOs as a classed tool mobilised to violently displace working class neighbourhoods. In doing so, we show how a fictionalised mantra of "necessity" combines neoliberal growth logics with their obscene underside—a stigmatisation logic that demonises poor urban neighbourhoods. CPOs can be used progressively, for example to abrogate the power of slum landlords for social democratic ends, yet with the increasing urbanisation of capital they more often target marginalised neighbourhoods in the pursuit of land and property valorisation. The growing use of CPOs as an exceptional measure in urbanisation, we argue, requires urgent attention in urban political struggles and policy practice.